2018
DOI: 10.1021/acs.organomet.8b00017
|View full text |Cite
|
Sign up to set email alerts
|

CO2/Epoxide Coupling and the ROP of ε-Caprolactone: Mg and Al Complexes of γ-Phosphino-ketiminates as Dual-Purpose Catalysts

Abstract: γ-Phosphino-ketimines Ph 2 PC[C(Me)O][C(Me)NAr] (Ar = 2,6-diisopropylphenyl, L 1 H; Ar = 2,6-difluorophenyl, L 2 H) were synthesized by treating deprotonated ketimines with PPh 2 Cl. Their Mg complexes [(L 1 ) 2 (THF)Mg] (1) and [(L 2 ) 2 (THF) 2 Mg] (2) were obtained in excellent yields from a reaction between LH and di-nbutylmagnesium in THF. Addition of a slight excess of trimethylaluminum to LH in toluene yielded the Al complexes [L 1 AlMe 2 ] ( 3) and [L 2 AlMe 2 ] (4). Complexes 1 and 3 displayed high ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The second example, [Mg(L R )N(SiMe 3 ) 2 ] 2 (where L R = [OCMe 2 CH 2 (CNCH 2 CH 2 NR)]), features a magnesium atom supported by a bidentate alkoxide-NHC ligand [38]. It is noteworthy that magnesium complexes with Mg-OR units have been shown catalyze the formation of polylactide [14,38,[40][41][42][43][44], the ring opening polymerization of ε-caprolactone [45], as well as the hydroboration of aldehydes and ketones [46]. The chemistry of beryllium continues to be severely understudied relative to the heavier group 2 elements and NHC-beryllium oxides are hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The second example, [Mg(L R )N(SiMe 3 ) 2 ] 2 (where L R = [OCMe 2 CH 2 (CNCH 2 CH 2 NR)]), features a magnesium atom supported by a bidentate alkoxide-NHC ligand [38]. It is noteworthy that magnesium complexes with Mg-OR units have been shown catalyze the formation of polylactide [14,38,[40][41][42][43][44], the ring opening polymerization of ε-caprolactone [45], as well as the hydroboration of aldehydes and ketones [46]. The chemistry of beryllium continues to be severely understudied relative to the heavier group 2 elements and NHC-beryllium oxides are hitherto unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous reports showed that some homoleptic complexes were indeed active in ROP of cyclic esters in the presence of external alcohol (Scheme ) . The Ejfler group developed a kind of hetero‐ and homoleptic molecular zinc complexes with one or two equivalents of aminophenolate ligand in 2008 (Scheme a) .…”
Section: Introductionmentioning
confidence: 99%
“…The homoleptic zinc complex (Scheme e) based on salicylaldiminato ligands synthesized by the Wu group needed to be activated by raising the temperature to 130°C . Some homoleptic magnesium complexes (Scheme f–h) produced PCLs in 15–60 min, with MWs diverging from theoretical MWs or broad MWD . Though the homoleptic metal complexes were not traditionally regarded as effective initiators for ROP of cyclic esters, these elegant studies showed that the homoleptic, bis‐ligated organometallic complexes can be a potentially effective catalytic system in ROP of lactides and lactones, especially in the presence of external alcohol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations